Can informal corporate governance mechanisms mitigate diversification discount? Evidence from Malaysia - Lee, Kian Tek *; Hooy, C. W. (Emerald, 2018)
Purpose: The purpose of this paper is to examine whether any specific informal corporate governance mechanisms under consideration in this study, namely, political connection, business group affiliation and ownership concentration, are able to mitigate the diversification discount for emerging-market diversified firms using Malaysia as an examination lab. Design/methodology/approach: The study uses a sample data of the entire non-financial public-listed firms in Malaysia over a 12-year period from 2001 to 2012. The generalized method of moments estimators are employed to account for the endogeneity of both corporate governance and diversification. Findings: This study finds that business group affiliation particularly with large size can help to mitigate the diversification discount whereby political connection and ownership concentration magnify the discount. The finding is robust to alternative diversification measurements, to alternative methods and to endogeneity bias. Research limitations/implications: This result implies that diversified firms with affiliation to large business groups are able to reduce the magnitude of the discounted value of diversification. Practical implications: This study helps managers, shareholders and investors to evaluate their current/future investments related to firms with diversified business segments. This study also provides implications for policymakers and regulatory bodies to assess the adequacy and competency of the current corporate governance frameworks in place. Originality/value: This study incorporates the country-specific institutional dimension in designing a research framework that is more relevant in examining the influential effect of governance-related characteristics on the diversification-firm value relationship in an emerging market.